Alternative SET/TAFI Promoters Regulate Embryonic Stem Cell Differentiation - Edupuganti, Raghu Ram (2017)
Embryonic stem cells (ESCs) are regulated by pluripotency-related transcription factors in concert with chromatin regulators. To identify additional stem cell regulators, we screened a library of endogenously labeled fluorescent fusion proteins in mouse ESCs for fluorescence loss during differentiation. We identified SET, which displayed a rapid isoform shift during early differentiation from the predominant isoform in ESCs, SETα, to the primary isoform in differentiated cells, SETβ, through alternative promoters. SETα is selectively bound and regulated by pluripotency factors. SET depletion causes proliferation slowdown and perturbed neuronal differentiation in vitro and developmental arrest in vivo, and photobleaching methods demonstrate SET's role in maintaining a dynamic chromatin state in ESCs. This work identifies an important regulator of pluripotency and early differentiation, which is controlled by alternative promoter usage.